2022
DOI: 10.1136/jitc-2022-005615
|View full text |Cite
|
Sign up to set email alerts
|

Crucial roles of circulating tumor cells in the metastatic cascade and tumor immune escape: biology and clinical translation

Abstract: Cancer-related deaths are mainly caused by metastatic spread of tumor cells from the primary lesion to distant sites via the blood circulation. Understanding the mechanisms of blood-borne tumor cell dissemination by the detection and molecular characterization of circulating tumor cells (CTCs) in the blood of patients with cancer has opened a new avenue in cancer research. Recent technical advances have enabled a comprehensive analysis of the CTCs at the genome, transcriptome and protein level as well as first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…Understanding the phenotypic changes in CTCs provides insights into the mechanisms that cancer employs to evade treatment and can guide future therapeutic development. This is particularly crucial given the impracticality of obtaining biopsies from patients’ metastatic sites. , …”
Section: Microfluidic-sers Ctc Analysis and Its Clinical Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the phenotypic changes in CTCs provides insights into the mechanisms that cancer employs to evade treatment and can guide future therapeutic development. This is particularly crucial given the impracticality of obtaining biopsies from patients’ metastatic sites. , …”
Section: Microfluidic-sers Ctc Analysis and Its Clinical Utilitymentioning
confidence: 99%
“…This is particularly crucial given the impracticality of obtaining biopsies from patients' metastatic sites. 100,101 CTCs also act as independent prognostic factors, and their presence in the blood post treatment is associated with a poor prognosis in various cancer types. During disease surveillance, their increased counts are correlated to a higher likelihood of metastasis and cancer aggressiveness.…”
Section: Clinical Utility Of Microfluidic-sers Platformmentioning
confidence: 99%
“…1 In the third phase, malignant cells fully escape from immune control to a point at which they become clinically detectable and become able to infiltrate adjacent tissues and ultimately generate distant metastases. 17,18 The three Es are also reflected in the means by which we intervene against cancer. Elimination may be achieved by prophylactic immunization, 19 as exemplified by the ability of human papillomavirus vaccination to protect against cervical carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, cancer cells that acquire the ability to avoid immune recognition or that weaken immune effectors selectively expand within the tumor 1 . In the third phase, malignant cells fully escape from immune control to a point at which they become clinically detectable and become able to infiltrate adjacent tissues and ultimately generate distant metastases 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, most CTC studies were performed in patients with advanced-stage cancer, where CTC numbers are usually much higher than in early stage. The next goal for CTC analysis is the detection and characterization of minimal residual disease (MRD) [ 12 ], since a number of clinical studies have shown that CTC detection in the peripheral blood of patients who lack any clinical or radiological signs of metastasis is related to recurrence [ 13 ] ( Figure 1 ). Towards this goal, the molecular characterization of CTC provides critical information for the presence of therapeutic targets and resistance mechanisms that is paramount for the management of cancer patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%